Atmospheric corrosion of low carbon steel, at different exposure angles, in a tropical environment - Jimenez-Salas, Ronald (2022)
In this research, the effect of the environment in a tropical region of central Costa Rica on the corrosion of low carbon steel was studied, with the objective of establishing the variation of the corrosion rate as a function of the exposure angle. For this purpose, specimens were placed at different angles (0°, 30°, 45°, 60° and 90°) in three stations along the Central Valley; environmental parameters such as humidity, wetting time, temperature and the presence of atmospheric pollutants, such as sulfates and chlorides, were also measured. As main results it was determined that the steel presented a linear increase of corrosion with the decrease of the angle with respect to the horizontal, likewise the corrosion is uniform in angles less than 60 degrees, presenting partial corrosion in high angles, especially for protected faces. Corrosivity is at a mild urban level, type C2, according to ISO standards.